"Being hooked" by a brand story: a view of regulatory focus. Issue 5 (11th May 2015) - Lin, Chien-Huang; Chen, Ming-Yi
Abstract : Purpose: – The aims of this study are twofold: to explore the influence of the typicality of brand story and regulatory focus on the effectiveness of argument strength and product evaluations and to examine the mediating role of being hooked. Design/methodology/approach: – The study performed two experiments which showed how the measured or induced regulatory focus of a consumer in a given situation moderates the relationship between typicality of the brand story and product evaluations. Findings: – The results show that prevention-focused individuals rely on the substance of the message after reading an atypical brand story, whereas promotion-focused individuals are more likely to be hooked by an atypical brand story. Moreover, the findings have also revealed that being hooked mediated the results of the interaction effects of the typicality of brand story and regulatory focus on product evaluation. Practical implications: – A better understanding of the interplay effects between the perceived typicality of brand story and the regulatory focus of target audiences has the potential to help marketers increase the persuasiveness of their communication messages. Originality/value: – To the authors' knowledge, this is the first piece of research to examine how the typicality of brand story and regulatory focus can influence the likelihood of a consumer being hooked. Moreover, the present study is among the first to show that regulatory focus is an important moderator of the effects of typicality, and this contributes to the literature of categorization theory.